2020
DOI: 10.4103/jfmpc.jfmpc_1172_20
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in paediatrics with intractable epilepsy in a large paediatric university hospital in Riyadh, Saudi Arabia

Abstract: Context: Epilepsy is said to be intractable when two or more trials of anticonvulsants fail to control the seizures. Literature suggests that intractable epilepsy carries a higher morbidity than controlled epilepsy in children and their caregivers. Aims: The aim of this study is to assess the quality of life (QOL) in children with intractable epilepsy (IE) in KASCH, a tertiary care hospital in Riyadh, Saudi Arabia. Settings and Design: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…However, there is a lack of evidence regarding these effects, especially in the Middle East in general and Saudi Arabia specifically. Another cross-sectional study conducted in the central region of Saudi Arabia, which aimed to explore similar objectives as ours, concluded that intractable epilepsy significantly affects QoL [ 12 ]. Based on this observation, we investigated whether there was an overall interregional difference between the central and western regions of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, there is a lack of evidence regarding these effects, especially in the Middle East in general and Saudi Arabia specifically. Another cross-sectional study conducted in the central region of Saudi Arabia, which aimed to explore similar objectives as ours, concluded that intractable epilepsy significantly affects QoL [ 12 ]. Based on this observation, we investigated whether there was an overall interregional difference between the central and western regions of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 88%
“…A similar study was published in Riyadh in 2020, which assessed the QoL of 59 pediatric patients with intractable epilepsy in a large pediatric university hospital. We used this as a reference for determining the minimal sample size [ 12 ]. However, when attempting to calculate the sample size using Raosoft.com sample size calculator, using the Centers for Disease Control's (CDC) nationwide prevalence of 0.6% for epilepsy, the estimated sample size was 10 with a 5% margin of error and a 95% confidence interval, which was deemed inadequate to yield statistically significant results.…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, adolescents with mental health problems have been neglected in HrQoL studies. In addition, a few clinical-based studies have analyzed the relationship between HrQoL and chronic physical diseases, such as Type 1 diabetes[ 25 ], epilepsy [ 26 ], overweight [ 27 ], and other chronic illnesses [ 28 ]. However, no studies have evaluated the relationship between HrQoL and adolescent mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…They have concluded that over two-thirds of children with epilepsy aged 7 to 18 years have reported being absent from school (7). Another study performed in Riyadh city, Saudi Arabia, assessed the quality of life of children patients with epilepsy before the pandemic of coronavirus, they found that Intractable epilepsy had a negative impact on many aspects of life, resulting in a low quality of life (8).…”
Section: Introductionmentioning
confidence: 99%